Improving sustainability of precast concrete sandwich wall panels through stone waste aggregates and supplementary cementitious material - Kumar, Pushpender; Kumar, Rajesh; Nighot, Nikhil Sanjay; Rahman, Mohd. Reyazur; Chidambaram, R. Siva; Khan, Shahnawaz; Surabhi, Surabhi (Applied Engineering and Technology, 2024)
This study aims to enhance the sustainability of precast concrete sandwich wall panels by replacing 100% of natural aggregates with stone waste and 30% of cement with supplementary cementitious materials. The panels, consisting of two 60 mm thick concrete wythes reinforced with 1% steel fibers, were connected using basalt fiber-reinforced polymer (BFRP) connectors and separated by high-density expanded polystyrene (EPS) insulation (30 kg/mÂ³). Full-scale panels were tested for flexural strength, showing that the inclusion of sustainable materials increased the failure load by 96% compared to conventional panels, with steel fiber-reinforced panels achieving a failure load of 110.5 kN. Panels incorporating stone waste aggregates demonstrated a 71% increase in strength compared to control samples. These results highlight that using stone waste and supplementary materials not only improves environmental sustainability but also enhances structural performance, making these panels a viable option for eco-friendly construction.